Hypereosinophilic syndrome presenting as peripheral neuropathy. Issue 715 (May 1985) - Bell, D.; Mackay, I. G.; Pentland, B.
Abstract : An unusual case of hypereosinophilic syndrome is described which presented with peripheral neuropathy with no evidence of cardiac involvement. The response to steroid therapy is documented and the literature on peripheral neuropathy in hypereosinophilic syndrome is reviewed.